Clinical and pharmacodynamic activity of bortezomib and decitabine in acute myeloid leukemia - Blum, William (American Society of Hematology, 2012)
We recently reported promising clinical activity for a 10-day regimen of decitabine in older AML patients; high miR-29b expression associated with clinical response. Subsequent preclinical studies with bortezomib in AML cells have shown drug-induced miR-29b up-regulation, resulting in loss of transcriptional activation for several genes relevant to myeloid leukemogenesis, including DNA methyltransferases and receptor tyrosine kinases. Thus, a phase 1 trial of bortezomib and decitabine was developed. Nineteen poor-risk AML patients (median age 70 years; range, 32-84 years) enrolled. Induction with decitabine (20 mg/m(2) intravenously on days 1-10) plus bortezomib (escalated up to the target 1.3 mg/m(2) on days 5, 8, 12, and 15) was tolerable, but bortezomib-related neuropathy developed after repetitive cycles. Of previously untreated patients (age ≥ 65 years), 5 of 10 had CR (complete remission, n = 4) or incomplete CR (CRi, n = 1); 7 of 19 overall had CR/CRi. Pharmacodynamic analysis showed FLT3 down-regulation on day 26 of cycle 1 (P = .02). Additional mechanistic studies showed that FLT3 down-regulation was due to bortezomib-induced miR-29b up-regulation; this led to SP1 down-regulation and destruction of the SP1/NF-κB complex that transactivated FLT3. This study demonstrates the feasibility and preliminary clinical activity of decitabine plus bortezomib in AML and identifies FLT3 as a novel pharmacodynamic end point for future trials. This study is registered at http://www.clinicaltrials.gov as NCT00703300.